PENGARUH LEVERAGE, PROFITABILITY, MATURITY, SIZE, DAN FREE CASH FLOW TERHADAP KEBIJAKAN DIVIDEN PADA SEKTOR PERBANKAN INDONESIA - Nurhaelis, Elis; Yazid, Helmi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This research aims to examine the Leverage, Profitability, Maturity, Size and Free Cash Flow toward dividend policy, Leverage measure by Debt to Asset Ratio (DAR), Profitability (ROA), Maturity, Size, and Free Cash Flow (FCF) on Dividend policy represented by the Dividend Payout Ratio (DPR). This research population is banking that is listed at the Indonesia stock exchange. The criteria research of samples data used on this research is government banks and private banks exists in Indonesia from 2012 up to 2016. Where in the research, banks pays dividends at shareholders. This study used a purposive sampling method. Of the data is processed using SPSS program version 24.0 by OLS regression approach (Ordinary Least Square). Analytical techniques used in this study consists of a descriptive statistic test, test of normality, a linear regression analysis, and test hypotheses through the analysis of the coefficient of determination (R2), model test research (statistical tests F), and partial (test test t statistics). The results of this study demonstrate that profitability (ROA) and Maturity has a significant effect on dividend policy. But the Leverage (DAR), Size and Free Cash Flow (FCF) is not significant effect on dividend policy.Â Keywords: Leverage, Profitability, Maturity, Size, Free Cash Flow, Dividend Policy.Â